2019
DOI: 10.1177/0091552119880941
|View full text |Cite
|
Sign up to set email alerts
|

Where to Go From Here? Toward a Model of 2-Year College Students’ Postsecondary Pathway Selection

Abstract: Objective: Empirical work explaining student mobility, particularly postsecondary pathways among 2-year college students, remains limited. This study examines the underlying process that drives 2-year college students into one or more pathways as they navigate higher education. Method: Drawing upon survey, transcript, and interview data from one transfer-focused and two comprehensive community colleges in a Midwestern state, this study uses a grounded theory approach to develop a conceptual model to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…The second trajectory is referred to as "detoured". This detoured group experiences delays in transfer and/or engages in "swirling", which, in itself, has many definitions (Wang and Pilarzyk, 2009;Soler, 2020;Wickersham, 2020), though, most generally is defined as backand-forth enrollment at different institutions. The third trajectory is the "deferred" student, which is a student that chooses to forego transfer after credential completion at the two-year college.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second trajectory is referred to as "detoured". This detoured group experiences delays in transfer and/or engages in "swirling", which, in itself, has many definitions (Wang and Pilarzyk, 2009;Soler, 2020;Wickersham, 2020), though, most generally is defined as backand-forth enrollment at different institutions. The third trajectory is the "deferred" student, which is a student that chooses to forego transfer after credential completion at the two-year college.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated the positive impact on STEM success for students that engage with undergraduate research (Brownell and Swaner, 2009;Eddy, 2014;Kilgo et al, 2015), though there are barriers to access for community college students which can be partially overcome through utilizing REU's (Research Experiences for Undergraduates) that specifically target 2-year and URM students. There is also a need to better understand the twoyear student population (Wickersham, 2020), especially the structural inequality and its impact on access and equity for underrepresented minoritized students (Bowleg, 2008 Though successful, the WSTPP has a number of limitations that the Inspire Scholars Program (ISP) was developed to address. One goal of the ISP was to "cast a wider net" through three key program eligibility changes to increase access to the program.…”
Section: Existing Barriersmentioning
confidence: 99%
“…Clark (1960) argues that community college serves a cooling out function in the United States, where students are essentially discouraged from pursuing a bachelor's degree through a transfer but are encouraged to take an associate degree as a terminal degree. However, the transfer rate has been one major concern in understanding the roles of community colleges (DiRamio, 2017;Wickersham, 2020). In view of students' instrumentalism toward education in Hong Kong, it is unsurprising that the option of community college in Hong Kong is essentially taken up by students who desire to get transferred to a bachelor's degree rather than to take an associate degree as a terminal degree (Ng & Cheng, 2001).…”
Section: The Community College Policy Launched In Ever More Competitive Hong Kongmentioning
confidence: 99%
“…We also borrow from Wickersham’s (2020) College Pathway (Re)Selection Model to explain community college students’ decision-making process when choosing between different postsecondary pathways. The College Pathway (Re)Selection Model defines the pathway decisions of community college students under one of two broad categories—lifetime decision making and short-term decision making.…”
Section: Introductionmentioning
confidence: 99%